TINJAUAN KINERJA PELAYANAN ANGKUTAN UMUM ANTAR KOTA PT ZONA SIKUMBANG JAYA RUTE BUKITTING - PAINAN - Kurnia Ramadani; Ishak Ishak; Yorizal Putra (Ensiklopedia Research and Community Service Review, 2023)
Abstract: This study aims to determine the performance of public transportation services and evaluate the performance of public transportation services on the Bukittinggi – Painan route. The method used by the researcher uses a Likert and Guttman scale. By distributing a questionnaire of 88 respondents. This research was conducted by means of a survey through the distribution of respondents' questionnaires. After that, the validity and reliability of the questionnaire were tested, then continued with data analysis of the research results. From the results of data analysis, it was obtained that taking the reliability test using 30 respondents to test reliability, the results of the Alpha coefficient of 0.723 were said to be reliable because the Alpha coefficient was above 0.600. The performance of public transportation services at PT zona Sikumbang Jaya rute Bukittinggi – Painan route is quite good, because in the search for high correlation validity results, the highest validity value is 0.966, and the validity results can also be seen from r_(count<r table) so that the data in the calculation is said to be valid.Keywords : Intercity Transportation Within Province, SPSS 25